The prognostic relevance of serum lactate dehydrogenase and mild bone marrow reticulin fibrosis in essential thrombocythemia. Issue 5 (20th March 2017) - Mudireddy, Mythri; Barraco, Daniela; Hanson, Curtis A.; Pardanani, Animesh; Gangat, Naseema; Tefferi, Ayalew
Abstract: The 2016 World Health Organization (WHO) diagnostic criteria for myeloproliferative neoplasms (MPN) underscore the prognostically‐relevant distinction between essential thrombocythemia (ET) and prefibrotic primary myelofibrosis (pre‐PMF). In addition, leukocytosis has been identified as an important prognostic marker in otherwise WHO‐defined ET. However, controversy remains regarding the objectivity of morphologic criteria in distinguishing ET from pre‐PMF and the precise prognostic cutoff values for leukocytosis. Serum lactate dehydrogenase (LDH) level might be a biologically more accurate measure of leukocyte turnover and a more sensitive marker of pre‐PMF, in otherwise WHO‐defined ET. In the current study of 183 consecutive patients with WHO‐defined ET, the presence of grade 1 bone marrow (BM) fibrosis did not affect presenting clinical or laboratory features; in contrast, increased serum LDH at diagnosis was associated with leukocytosis ( p = .002), thrombocytosis ( p < .001), palpable splenomegaly ( p = .03) and higher international prognostic score (IPSET) ( p = .002); serum LDH did not correlate with BM fibrosis, JAK2 / CALR / MPL or TET2/ASXL1 mutations. In univariate analysis, risk factors for survival included age ≥60 years ( p = .002; HR 10.2, 95% CI 2.3‐44.6), male sex ( p = .02; HR 3.2, 95% CI 1.2‐8.2), leukocyte count ≥15 × 10 9 /L ( p = .007; HR 4.7, 95% CI 1.5‐14.6), and increased serum LDH ( p = .002; HR 3.7, 95% CI 1.5‐9.1), but not BM fibrosis ( p = .17). In multivariable analysis, age, sex and serum LDH remained significant; serum LDH also remained significant, in the context of IPSET ( p = .003) and in patients with leukocytosis ( p = .003). We conclude that serum LDH level carries an independent prognostic value for survival in ET and might represent a biologically more accurate surrogate for leukocytosis.